2015
DOI: 10.1007/s00228-015-1906-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethylphenidate: availability, patterns of use, and acute effects of this novel psychoactive substance

Abstract: This review of the scientific and grey literature has demonstrated that the acute harms associated with its use are stimulant in nature and that ethylphenidate is widely available to users over the Internet, with significant discounts for bulk purchases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Parks et al, also indicate that in 9 of the 17 reported cases ethylphenidate was being injected. Previous studies have utilised internet forum case reports to investigate the routes of administration of ethylphenidate [8,9]. In the case reports ethylphenidate is most commonly insufflated (52.5%) followed by multiple routes (16.7%), oral ingestion (11.6%) and intravenous injection (9.6%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Parks et al, also indicate that in 9 of the 17 reported cases ethylphenidate was being injected. Previous studies have utilised internet forum case reports to investigate the routes of administration of ethylphenidate [8,9]. In the case reports ethylphenidate is most commonly insufflated (52.5%) followed by multiple routes (16.7%), oral ingestion (11.6%) and intravenous injection (9.6%).…”
Section: Resultsmentioning
confidence: 99%
“…In the case reports ethylphenidate is most commonly insufflated (52.5%) followed by multiple routes (16.7%), oral ingestion (11.6%) and intravenous injection (9.6%). Minor routes include rectal insertion, sublingual insertion, smoking and intramuscular injection [8].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations